Analisis Ketahanan Infrastruktur Pengelolaan Air Limbah Domestik di Jakarta (Studi Kasus Jakarta Sewerage Development Project) - Marzio, Aldy; Ras, Abdul Rivai; Riyanta, Stanislaus (Publikasi Indonesia, 2025)
This research aims to analyze the resilience of domestic wastewater management infrastructure in Jakarta, especially the Jakarta Sewerage Development Project (JSDP), and formulate a number of policy recommendations. The method used in this paper is qualitative with an analytical type. In conducting the analysis and formulating policy recommendations, the researcher is based on an incremental model that emphasizes improvements to existing policies. The results of this paper indicate that the development of JSDP is a policy that is very much needed by the community to overcome the minimal coverage of domestic wastewater management services in Jakarta which has an impact on health. In order for JSDP to be a resilient infrastructure as well as an infrastructure to support social and economic resilience, the application of six principles of infrastructure resilience is needed. In addition, active community involvement in the decision-making process is also needed to create more measurable conditions and mutual supervision. Although the development of JSDP has reflected the goals of sustainable development, this project still poses challenges to the environmental dimension because it triggers deforestation and reduces the existence of green open spaces. Therefore, the researcher formulates several policy recommendations including general recommendations, recommendations related to technical and construction issues, recommendations related to environmental issues, recommendations related to social and institutional issues, and recommendations related to financing issues.